Noção de representação na Ciência da Informação: concepções a partir da filosofia de Arthur Schopenhauer - Silva, Julianne Teixeira e (2016)
It is presented an enlargement of the notion field of information representation in the context of Information Science, bringing the trace of epistemic trajectory, from Classical Antiquity and its western linear thought, passing by its heritages, until the perceived connections between Information Science and the thought of Arthur Schopenhauer. The thesis that it would be found such resource to the bases of this enlargement in the thought of Schopenhauer, which defends the comparison and reflection between the philosophic aspects of the thought of the author and the theoretical bases of Information Representation in the ambit of Information Science, in Brazil, it indicated, from the reflections and arguments enrolled, that there are relevant elements in the thought of Schopenhauer, in which there are points of theoretical convergence that can ground these debates in the ambit of Information Science, mainly in the Theory of Knowledge developed by Schopenhauer, especially in its notion of conceptual spheres.